Double cross - Prowse, Philip (Cambridge English readers. Level 3, 1999)
A fast-moving international thriller set in Scandinavia, London, and southern Africa. A politician nearly dies in Stockholm, and secret agent Monika Lundgren chases the would-be killer. As she races across the world she meets a strange football team, a rock musician, and a madman with dreams of world power.